2010
DOI: 10.1055/s-0029-1219836
|View full text |Cite
|
Sign up to set email alerts
|

Enamine-Based Domino Strategy for C-Acylation/Deacetylation of Acetoacetamides: A Practical Synthesis of β-Keto Amides

Abstract: A practical three-step route for C-acylation/deacetylation of acetoacetamides is described. Initial enamination of the acetoacetamides with Boc-monoprotected ethylenediamine provides benamino amides, which are acylated at the a-carbon with excellent selectivity. The C-acylated derivatives undergo domino fragmentation in acidic media to give the corresponding b-keto amides accompanied by 2-methyl-4,5-dihydro-1H-imidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…Initially we tried a procedure developed earlier by us for simpler β-keto amides (30 min in neat TFA, then aqueous NaOAc) [ 22 ]. In contrast to the preparation of non-functionalised β-keto amides, here these conditions led to satisfactory yields of keto amides 5 only for substrates 3 with R 3 ≠ H ( 3g – l ), while in all other cases ( 3a – f , R 3 = H) gave significant amounts of pyrrolin-4-ones 6 as competing side products ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially we tried a procedure developed earlier by us for simpler β-keto amides (30 min in neat TFA, then aqueous NaOAc) [ 22 ]. In contrast to the preparation of non-functionalised β-keto amides, here these conditions led to satisfactory yields of keto amides 5 only for substrates 3 with R 3 ≠ H ( 3g – l ), while in all other cases ( 3a – f , R 3 = H) gave significant amounts of pyrrolin-4-ones 6 as competing side products ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dianion of silylated acetamide is another such example, although with very limited scope [ 21 ]. A contribution of ours in this area is the application of ethylenediamine-derived β-enamino amides as synthetic equivalents of primary and secondary amide enolate synthons in reactions with acid chlorides [ 22 ]. To extend the scope of the methodology, we now have explored the acylation of these reagents with suitably activated amino acids, in order to prepare functionalised β-keto amides, bearing a protected amino group in their side chain.…”
Section: Introductionmentioning
confidence: 99%
“…Our rst task was to establish a sequence which provided access to oxazolidines of type 2 (Scheme 1) with a diversity of substitution patterns, and which would ultimately translate into multiple ring substitution patterns on pyroglutamate 3. Critical to the success of this strategy was the simultaneous development of a direct method for the preparation of gsubstituted b-ketoesters by elaboration of Meldrum's acid, 16 substrates which are of particular interest due to their scope for further functionalisation; analogous ring openings on dioxinones have been recently reported. 17 Starting from substituted acetyl chlorides 4a-d, conversion to the corresponding acylated Meldrum's acids 5a-d proceeded in excellent yield (Scheme 2) using methodology which has recently been reported.…”
mentioning
confidence: 99%
“…Although these data were not entirely corroborated by later publications from the same group [3] and others [4][5][6], the interest drawn by this natural product has led to the preparation of many analogues, some with promising bioactivity [4][5][6][7][8]. Considering the current interest in this topic and the ongoing investigations of the structure-activity relationships, we saw an opportunity to contribute to the availability of structurally diverse Santacruzamate A analogues with our method for β-keto amide synthesis [9]. In a previous publication we demonstrated that this enamine-based domino approach provides access to β-keto amides IV functionalized with protected amino group in the side chain (Scheme 1, R 1 = H, Ph) [10].…”
Section: Introductionmentioning
confidence: 83%
“…All reagents and solvents were purchased from commercial suppliers (Sigma-Aldrich or Merck, Darmstadt, Germany) and were used without further purification. Boc-monoprotected ethylenediamine [11], acetoacetamides 1 [12,13], and enaminoamides 2 [9] were prepared according to the published procedures. NMR spectra were run on Bruker Avance AV600 (600/150 MHz 1 H/ 13 C) spectrometer (Bruker, Billerica, MA, USA) at BAS-IOCCP-Sofia and chemical shifts (δ, ppm) are downfield from TMS.…”
Section: Methodsmentioning
confidence: 99%